A quantitative method to describe the flow characteristics of an oscillating flow including porous media. (April 2018) - Ni, Mingjiang; Peng, Hao; Sultan, Umair; Luo, Kun; Xiao, Gang
Highlights: Combined experimental and simulation study is carried out on oscillating flows. The cycle rate through porous media, a particularly basic parameter, is proposed. A modified dimensionless fluid displacement is introduced using the cycle rate. Equations for phase difference and cycle-averaged friction factor are proposed. A quantitative method to describe flow characteristics is developed. Abstract: The flow characteristics of an oscillating flow including porous media are very important for designing oscillating-flow-based devices. A combined experimental and simulation study is carried out to provide a comprehensive quantitative understanding of the oscillating flows. The cycle rate through porous media, a particularly basic parameter, is proposed based on the dimensionless pressure drop as a correction factor for the similarity parameters of the oscillating flows. A modified dimensionless fluid displacement is introduced based on the cycle rate, and a correlation equation is proposed to calculate the cycle-averaged friction factor of porous media. Significant phase difference (7–71°) is observed between the movements of gas inside porous media and pistons, which increases with the increasing pressure drop of porous media. Another correlation equation is proposed to predict the phase difference. It should be noted that the pressure drop of porous media would also affect the flows inside other heat exchangers between cylinder and porous media. The mass flow rate next to the cylinder is very different from that adjacent to the porous media in terms of amplitude and phase difference. Mass flow rates at different cross sections vary linearly with the volume between the piston upper surface and the monitored cross section. Finally, a quantitative method is proposed to describe the flow characteristics of an oscillating flow including porous media, which is expected to improve the design methods of oscillating-flow-based devices.